Spatial variation and determinants of skilled birth attendant delivery among women of reproductive age in Ethiopia: a spatial and multilevel analysis - Yibeltal Addis Mekuria; Betelhem Gelaw Zeleke; Getahun Workineh Mekonen; Tewabe Malede Chekol (BMC Pregnancy and Childbirth)
Abstract Background Delivery assisted by skilled birth attendants is essential for maternal and newborn health because most maternal and infant deaths occur during childbirth. Ethiopia continues to use skilled birth care services that are far below acceptable standards. There are also regional variations in skilled birth attendant delivery services in the country. Therefore, this study explored the spatial distribution and factors associated with the use of skilled birth attendants in Ethiopia based on nationally representative EMDHS 2019 data. Methods This study included a weighted sample of 5,527 women who had given birth within the 5 years prior to the survey year. ArcGIS version 10.7 was used to visualize the geographic variations, and Kulldorff’s SaTScan version 9.6 was used to identify significant purely spatial clusters. A multilevel mixed-effects logistic regression model was fitted to identify determinant factors of skilled birth attendant delivery using STATA 17. Results The number of women who delivered with the assistance of skilled birth attendants was 2,740 (49.6%) and distributed non-randomly across the regions of the country. Low clustering of skilled birth attendant delivery was detected in the Afar, Amhara, Benshangul-Gumuz, Gambela, Oromia, and Somali regions, whereas high clustering was detected in the Addis Ababa, Dire Dawa, and Harari regions. Maternal education level, parity, wealth index, region, place of residence, and community poverty level were significant predictors of skilled birth attendant delivery. Conclusion and recommendation Skilled birth-assisted delivery remains below national and international acceptable standards and is associated with geographic variation across the country. If it continues at the current pace, it will be difficult to achieve national and international targets. Therefore, a geographic-specific intervention should be launched by the government and respective local administrators, supported by local research in regions with low-skilled birth attendant delivery, to tackle individual and aggregate community-level determinants.